Organic Amendment Under Increasing Agricultural Intensification: Effects on Soil Bacterial Communities and Plant Productivity - Mas-Carrió, Eduard; Dini-Andreote, Francisco; Brossi, Maria Julia de Lima; Salles, Joana Falcão; Olff, Han (Frontiers in Microbiology, 2018)
The soil microbiome is a complex living network that plays essential roles in agricultural systems, regardless of the level of intensification. However, the effects of agricultural management on the soil microbiome and the association with plant productivity remain largely unclear. Here, we studied the responses of three soil systems displaying distinct levels of agriculture intensiveness (i.e., natural, organic, and conventional soil management) to experimentally manipulated organic farming amendments (i.e., dung and earthworms). We aimed at (i) identifying the effect on plant productivity and (ii) elucidating the degree of shifts in bacterial communities in response to the applied organic amendments. We found plant productivity to be lower with increasing agricultural intensification. Bacterial communities shifted distinctively for each soil management to the organic amendments applied. In brief, greater changes were observed in the Conventional management comparatively to the Organic and Natural management, an effect largely driven by dung addition. Moreover, we found evidence that the level of agricultural intensiveness also affects the timespan for these shifts. For instance, while the Natural system reached a relatively stable community composition before the end of the experiment, treatments of conventional soil management did not. Random forest analyses further revealed an increasing impact of introduced taxa from dung addition aligned with increasing agricultural intensification. These analyses further suggested that earthworms regulate the introduction of species from dung into the soil bacterial community. Collectively, our results contribute to a better understanding of the outcomes of organic amendments on soils under distinct levels of agriculture intensiveness, with implications for further development in soil restorations practices.